Mechanism of online emotional support accompany group for stress: The role of social support - Zhang, Yingjun; Huang, Heliang; Tang, Daisheng; Lu, Xiaohua; Fan, Fumin; Pan, Jingyi (Frontiers in Psychology, 2023)
Objective: To investigate the effect of social support on stress, and to clarify the effect and mechanism of Online Emotional Support Accompany Group (OESAG). Methods: The group members who signed up for the public welfare project "Psychological Rehabilitation Group Psychological Service under the COVID-19 Pandemic" were divided into the treatment group, the control group, and the blank group with 37 members each. The treatment group received OESAG intervention, the control group received online time management group intervention, and the blank group was the waiting group. The three groups of subjects were synchronously tested before and after the intervention group. Results: After the OESAG intervention, compared with the control group and the blank group, the treatment group showed that perceived social support was improved, and loneliness and stress were decreased. Conclusion: Improving social support can effectively reduce stress. OESAG can effectively improve social support and so too decrease stress. This study could help in designing effective psychological intervention measures to reduce the degree of stress symptoms and enhance both personal and social levels of coping with stressful events.